Professionalization of Human Resource Management in China: A Comparison Study to Law and Accountancy - ZHAO, lingling (Advances in Social Sciences Research Journal, 2018)
This paper aims to explore the development of HR profession in China in a comparative perspective. The author assessed the degree of HR professionalization in China through Fanning’s (2011) nine-characteristic model of HR profession. To better understand the extent of HR professionalization, the case of established professions—law and accountancy—are analyzed. Particularly, the professionality continuum in each profession is illustrated. In this paper, research questions concerning whether the HR profession is a semi or full profession, to what degree HR profession stands in the Chinese context, and how HR professionals can become more professionalized are answered.